Reverse Process Effectiveness as a Mediator of Return Volume Uncertainty, Return Information Quality, and Return Decision Quality on Warehouse Operational Performance in Indonesian FMCG Companies - Atik Fauziah Hadad; Erna Mulyati; Maniah Maniah (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
In the fast-moving consumer goods (FMCG) industry, the return of products to the warehouse is often an unplanned occurrence with an uncertain quantity, but the academic research on this is still not as advanced as the practice. Previous research is contradictory about the effect of return volume uncertainty, return information quality, and return decision quality on the operational performance of a warehouse, and the link between those variables through the reverse process effectiveness is not yet conclusively proven, particularly in the FMCG warehouse in Indonesia. In this study, return volume uncertainty, return information quality and return decision quality are directly and indirectly tested for their impacts on warehouse operational performance, while the reverse process effectiveness acts as a mediator. The data was obtained from 138 employees, supervisors, and managers in warehouses at FMCG companies in Indonesia based on cross-sectional survey analysis using the method of Partial Least Squares (PLS) Structural Equation Modeling. Return information quality had a direct impact on warehouse operational performance, whereas return volume uncertainty and return decision quality only had indirect implications when they had an impact on reverse process effectiveness. The novelty here is to demonstrate that the effectiveness of reverse process can serve as the hinge on which the benefits of information quality, decision quality and volume-uncertainty management can become tangible in the warehouse.